Flexible work arrangements in small and medium enterprises: incidence, motivations, advantages and disadvantages - Freches, Maria Helena Ferreira (2018)
Purpose - Examine SMEs' motivations for using flexible work arrangements (FWA). Analyse the incidence of different types of FWA and explore employers’ perceptions of the advantages and disadvantages of those arrangements. Methodology - Exploratory study based on semi-structured interviews to SMEs’ managers operating in Portugal. Findings - The evidence suggests that the determined duration contract is the most frequent FWA used by SMEs. The findings indicate that the motivations for the use of FWA can be aggregated in voluntary, pull and push factors. The most mentioned factors were voluntary. Furthermore, the advantage and disadvantage most mentioned were, respectively, cost reduction and the decrease of productivity amongst flexible employees.